Angiotensin II induces reorganization of the actin cytoskeleton and myosin light-chain phosphorylation in podocytes through rho/ROCK-signaling pathway*. (7th February 2016) - Wang, Siyuan; Chen, Cheng; Su, Ke; Zha, Dongqing; Liang, Wei; Hillebrands, JL; Goor, Harry van; Ding, Guohua
Abstract: Aims In the present study, we have evaluated the effect of angiotensin II (Ang II) on actin cytoskeleton reorganization and myosin light-chain (MLC) phosphorylation in podocytes to demonstrate whether the Rho/Rho-associated coiled kinase (ROCK) pathway is involved podocyte injury.Methods Eighteen male Sprague–Dawley rats were divided into three groups and treated with Ang II, saline or telmisartan. Morphological changes were studied at 28 days after treatment. Immunohistochemistry and Western blotting were used to determine the renal expression of p-MLC and ROCK2. Cultured podocytes were treated with Ang II (10 −7 M) with or without Rho-kinase inhibitor (Y27632, 10 −6 M) for variable time periods. F-actin was visualized with fluorescein isothiocyanate (FITC)-conjugated phalloidin or tetraethyl rhodamine isothiocyanate (TRITC)-conjugated phalloidin. p-MLC expression was evaluated by immunofluorescence and Western blot. The activation of Rho/ROCK was evaluated by Western blot.Results The expression of p-MLC in glomeruli increased significantly in rats treated with Ang II when compared to the control rats as shown by Western blot ( p < 0.05). In cultured podocytes, Rho A and ROCK2 increased after incubation with Ang II. Ang II increased the expression of ROCK2, which was accompanied with altered morphology, redistribution of actin and increased phosphorylation of MLC. The distribution of actin changed to a large extent, although overall quantitative differences were not observed. Addition of Y-27632 to podocytes treated with Ang II could ameliorate F-actin cytoskeleton remodeling and the increment in p-MLC expression.Conclusion Ang II-induced podocyte cytoskeleton protein expression changing through the RhoA/ROCK2 p-MLC/F-actin pathway.